2015
DOI: 10.1039/c4cy01070a
|View full text |Cite
|
Sign up to set email alerts
|

Amidinate group 4 complexes in the polymerization of olefins

Abstract: The current perspective will present the use of amidinate group 4 complexes in α-olefin polymerizations. We will present the structural studies of the complexes bearing various numbers of amidinates as spectator ligands, with a special emphasis on the bisIJamidinate) group 4 systems. The mechanistic studies elucidate the influence of various reaction conditions on the behaviour of the reactive species. Additionally, the study of the active species by techniques such as EPR spectroscopy and MALDI-TOF spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 110 publications
(178 reference statements)
0
15
0
Order By: Relevance
“…Amidinates are p-electron rich chelating ligands, whose coordination chemistry has been extensively studied across the periodic table. [17][18][19][20][21][22] These complexes have seen applications in homogenous catalysis 46 (in particular, olen polymerization 19,47 ). Amidinates are the nitrogen-analogues of carboxylates, containing two nitrogen atoms that can coordinate to metals as monodentate, bidentate, or bridging ligands (Fig.…”
Section: Nhc-cdis As Ligandsmentioning
confidence: 99%
“…Amidinates are p-electron rich chelating ligands, whose coordination chemistry has been extensively studied across the periodic table. [17][18][19][20][21][22] These complexes have seen applications in homogenous catalysis 46 (in particular, olen polymerization 19,47 ). Amidinates are the nitrogen-analogues of carboxylates, containing two nitrogen atoms that can coordinate to metals as monodentate, bidentate, or bridging ligands (Fig.…”
Section: Nhc-cdis As Ligandsmentioning
confidence: 99%
“…Complexes of hafnium have been predominantly used as Lewis acid catalysts in various organic transformations, such as the polymerization of cyclic esters, and as catalysts for the homo‐ and copolymerization of α‐olefins . Recently, Hf‐MOF compounds have been used as active catalysts for the activation of small molecules .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Many of them are promising homogeneous catalysts e.g. for olefin polymerization and hydroamination reactions, [11][12][13][14][15] whereas certain alkyl-substituted complexes are sufficiently volatile to be useful precursors for ALD (atomic layer deposition) and CVD (chemical vapor deposition) processes. [16][17][18][19][20][21][22][23][24] Recent contributions to this field clearly revealed that the use of unsymmetrically substituted amidinate and guanidinates ligands leads to further improved volatility of the respective transition metal and lanthanide complexes.…”
Section: Introductionmentioning
confidence: 99%